Bahasa Persuasi dalam Video YouTube Food Vlogger MGDALENAF - Salsabila, Imelda Febi; Harum Munazharoh (Universitas Muhammadiyah Surakarta, 2024)
A food vlogger's language of persuasion plays an important role in influencing viewership. It can arouse curiosity, whet appetites, and create emotional attachments with video viewers. In the midst of increasing content competition, the urgency of this study is to revisit the accuracy of word choice and easy-to-understand delivery to attract viewers. This article aims to identify persuasive forms in the YouTube videos of food vlogger MGDALENAF. The method used in this research is a qualitative method. The video transcription process uses the listening method, then the persuasive forms of MGDALENAF's speech are analyzed using the commensurate method and presented informally. The results of this study show a variety of assertive, directive, and expressive speech acts for certain purposes. Assertive speech acts are used for convincing actions. Directive speech acts are used for suggestion and invitation. Expressive speech acts are used for the act of praising. The dominance of speech used by MGDALENAF food vloggers is in the form of statement sentences and command sentences. The persuasion language used by MGDALENAF food vloggers is personal, casual, and not pushy. This casual nature then has an impact on the number of video viewers and the increasing interest of viewers to visit the culinary recommendations suggested by MGDALENAF food vloggers.